PENGARUH PEMBELAJARAN BERBASIS PROYEK TERHADAP HASIL BELAJAR DAN KEAKTIFAN SISWA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Siti Amallyah Hasanah; Ujiati Cahyaningsih; Budi Febriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to examine the effect of project-based learning (PjBL) on student learning outcomes and engagement in natural and social sciences (IPAS) at the elementary school level. This study was driven by low academic achievement and low student participation in IPAS classes, which generally use traditional teaching methods. This study used a quantitative approach with a non-equivalent control group design, with fifth-grade students from SDN Heuleut 1 participating in both experimental and control groups. Expert evaluation confirmed the feasibility of the PjBL learning tool (90.90%), and student feedback indicated high applicability (88.43%). The t-test showed a significant improvement in the experimental group (t-value 15.75 > t-value 2.045), with an average pre-test score of 55.08 increasing to 82.27 in the post-test. Furthermore, student participation in the experimental class also increased significantly. These findings indicate that PjBL is an effective approach to improve student achievement and engagement in IPAS learning at the elementary school level.